e-LIS, the digital repository for information, documentation and communication science publications (Confluenţe Bibliologice, 2021)
The e-LIS digital repository is a strategic tool to developing coherent approaches on capturing, identifying, storing and retrieving professional library content. In the article he agreed on the need for professional documentation from a credible source with relevant digital content.
Keywords: databases; electronic resources; information services; open science